Values and identities of the regional elite - T. A. Bevz, (Ukrainian Cultural Studies, 2020)
The article focuses on values as the basis of conscious choice. Values determine the future, determine the unity, cohesion of society and self- identification. Values are produced, distributed by elites and perceived by different social groups. The regional political elite is a certain group with a kind of corporate self-consciousness, its own independent system of values, which are fixed with help of certain external attributes, a system of selecting new members.The regional political elite was the creator of values and meanings in the politics of the region and played a significant role in shaping values, ideological preferences, views and attitudes to any political events, phenomena and processes.The policy of regional identity is conditioned by the culture of regional elites, their ideas about the past and future of the region and the country. After all, historical memory is an important element of national identity. The basic factor for the regional political elite of Sumy region in the processes of actualization of regional identities was the symbolic representation of the past, first of all, the history of the region.Most representatives of the Sumy regional political elite declared the values of paternalism, cooperation and democracy as a priority. The manifestation of political identity was a set of values, principles and motivations that representatives of the regional political elite recognize as basic for their political group. The regional political elite of Sumy region was the bearer of ideas and values, which were characterized by regional identity, regional interests and values, common history. Identity markers for the regional political elite of Sumy region were Ukraine as a homeland; Sumy region as a region it manages, business center, place of residence; public holidays as mechanisms of symbolic representation; historical memory, history of the region and history of the Cossacks.
Keywords: values, identities, regional elite, identity markers, Sumy region